Legal Protection for Creditors Regarding Default and Unilateral Transfer of Fiduciary Guarantee Vehicles Based on the Principle of Justice - Hirwansyah, Hirwansyah; Heber Ambuwaru , Jesse (Riviera Publishing, 2023)
Indonesian people generally buy private vehicles by using credit facilities or making monthly payments to finance companies to own their vehicles. Vehicles purchased on credit are bound by using fiduciary guarantees prone to being pawned, rented out and transferred by the debtor unilaterally. The reason was due to default so that the fiduciary guarantee vehicle was diverted so that it could be confiscated by POLRI investigators to be used as evidence. As a result of the unilateral transfer of the debtor, the creditor suffers a loss, so that the creditor must be legally protected. The purpose of this research is to find out and analyze the legal protection for credit related to violations and diversion of vehicles based on the principle of justice. The method in this research is qualitative research with empirical and normative juridical approaches. Empirical juridical research prioritizes secondary data, books, laws and regulations and examines positive legal principles from literary data and comparative law. The fiduciary giver must be responsible, carry out his obligations and keep the collateral object under his control. However, in reality it does not rule out the possibility of the Fiduciary Guarantee object changing hands or transferring control to a third party because it is transferred by the debtor, usually due to economic factors. The existence of Law no. 42 of 1999 concerning guarantees in Indonesia which are lex specialis derogat legi general, is one of the legal principles which implies that specific legal rules will override general legal rules.